A 3-slice cardiac quantitative native and post-contrast T1 and T2 MRI protocol requiring only four BHs using a 72-channel receive array coil - Klarenberg, Hugo; Gosselink, Mark; Siddiqui, Fasiha; Coolen, Bram F.; Nederveen, Aart J.; Leiner, Tim; Lamb, Hildo J.; Boekholdt, S. Matthijs; Strijkers, Gustav J.; Froeling, Martijn (Frontiers in Cardiovascular Medicine, 2023)
Current practice to obtain left ventricular (LV) native and post-contrast T1 and T2 comprises single-slice readouts with multiple breath-holds (BHs). We propose a multi-slice parallel-imaging approach with a 72-channel receive-array to reduce BHs and demonstrate this in healthy subjects and hypertrophic cardiomyopathy (HCM) patients.A T1/T2 phantom was scanned at 3T using a 16-channel and a novel 72-channel coil to assess the impact of different coils and acceleration factors on relaxation times. 16 healthy participants (8 female, age 28.4±5.1 years) and 3 HCM patients (3 male, age 55.3±4.2 years) underwent cardiac-MRI with the 72-channel coil, using a Modified Look-Locker scan with a shared inversion pulse across 3 slices and a Gradient-Spin-Echo scan. Acceleration was done by sensitivity encoding (SENSE) with accelerations 2, 4, and 6. LV T1 and T2 values were analyzed globally, per slice, and in 16 segments, with SENSE=2 as the reference.The phantom scans revealed no bias between coils and acceleration factors for T1 or T2, except for T2 with SENSE=2, which resulted in a bias of 8.0±6.7ms (p<0.001) between coils. SENSE=6 enabled T1 mapping of three slices in a single BH, and T2 mapping of three slices within two BHs. In healthy subjects, T1 and T2 values varied. We found an average overestimation of T1 in 3 slices of 25±87ms for SENSE=4 and 30±103ms using SENSE=6, as compared to SENSE=2. Acceleration resulted in decreased signal-tonoise; however, visually insignificant and without increased incidence of SENSE-artifacts. T2 was overestimated by 2.1±5.0ms for SENSE=4 and 6.4±9.7ms using SENSE=6, as compared to SENSE=2.Native and post-contrast T1 measurements with SENSE=4 and ECV quantification in HCM patients was successful.The 72-channel receiver-array coil with SENSE=4 and 6, enabled LV-tissue characterization in three slices.Pre-and post-contrast T1 maps were obtained in a single BH, while T2 required two BHs.